PERANCANGAN SISTEM INFORMASI AKUNTANSI DALAM MENGEMBANGKAN EFISIENSI PERUSAHAAN - VILANDA, IKA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
The use of computers in the company indicates that the technology has developed very rapidly. Not only big companies, medium and small companies are already using the computer as the main media in automating its business processes. The company's long-standing, also changed the original management system to manually switch to using a computer. This is because with a computer would be more appropriate business process and it takes a long time. Computer as a medium in carrying out information and control system business processes to fit the company's goals. The purpose of the company's top managers as determined by decision makers within the company. Information systems are built by the company should have benefits in achieving its objectives. Over the company's information systems, will be found to problems that could hinder the course of the business process. The problem that often arises is not the system goes well. So that the information provided is not useful in managerial decision making. Very useful for managerial decisions to regulate the course of the company. Design of information systems designed to meet all the criteria that are not on the old system. System design is the development of enterprise information systems. System design through the process of identifying problems, analyzing requirements, designing systems, system testing, and evaluating the system. With the design of information systems is expected to improve the performance of the company, because the measurement of company performance based on efficiency and effectiveness.